The Impact of eHealth and mHealth on doctor behavior and patient involvement: an Israeli and Portuguese comparative approach - Catan, G. (2017)
Based on the experience of a Short Term Scientific Mission (STSM) promoted by COST Net and developed in CIES/ISCTE-IUL (Portugal), this paper presents a reflection about the implementation of Information & Communication Technologies (ICT) in the healthcare sector in Israel and Portugal. Specifically, we focus on the impacts of ICT or eHealth on patient empowerment, as perceived by doctors and managers in order to better comprehend the role of national policy and explore the options for building a national strategy regarding ICT in healthcare. The experience of the Portuguese healthcare system was selected and compared to the results found in a similar research in Israel. Methodologically, in-depth interviews with the Ministry of Health, the private sector, patients associations and researches were used to collect data. Purposeful sampling was used to select respondents, and secondary sources were used for triangulation. The findings of the research work show that the increased deployment of ICT has furthered patient empowerment (1). From the doctors' perspective, while ICT has provided more information in the long-run, changes of these magnitudes were not easy in the beginning. These findings were similar in both countries. The work concludes that ICT tools were successfully implemented and the general perception is that they have been beneficial. The work provides information in order to understand and improve ICT services. Additionally, the results suggest alternatives for future investments in these technologies.